Head-To-Tail and Heteroleptic Pentanuclear Circular Helicates - Allen, Kirsty E; Faulkner, Robert A; Harding, Lindsay P; Rice, Craig R; Riis-Johannessen, T; Voss, Melanie L; Whitehead, Martina (Angewandte Chemie (International ed.), 2010)
Everybody form a circle: Careful design of ligand strands and their reaction with Cu2+ ions leads to the formation of the title helicates. Incorporation of differing numbers of N‐donor units within a ligand strand containing a phenyl spacer results in a pentanuclear head‐to‐tail circular helicate, whereas reaction of two different ligands results in a heteroleptic pentanuclear circular helicate (see picture; green: Cu, red and blue: ligands).